Comparison of the results of some serological tests for bovine brucellosis. - Chappel, R. J. (Cambridge University Press, 1978)
A total of 1887 bovine sera positive to the Rose Bengal plate test were subjected to other serological tests for bovine brucellosis: the complement fixation test using warm fixation (CFTW),the serum agglutination test (SAT) and the radioimmunoassay (RIA). The SAT was generally much less sensitive than the CFTW. Many sera, however, gave positive reactions in the SAT but no reaction in the CFTW or the RIA. These SAT reactions were attributed to IgM antibody. Comparison between the results of the CFTW and the RIA led to the conclusion that 200 ng could be used as a minimum diagnostic reaction in the RIA.